1989
DOI: 10.1515/zna-1989-0912
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Deuterium Hyperfine Structure in the Rotational Spectrum of Piperidine

Abstract: We reinvestigated by microwave Fourier transform spectroscopy the rotational spectra of the axial and equatorial isotopomers of piperidine and N-deutero piperidine. The rotational, centrifugal, and nitrogen quadrupole coupling constants were improved, the deuterium quadrupole coupling constants were determined. The principal coupling tensor elements for nitrogen were estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“… a Transitions were deperturbed for 14 N and 2 H quadrupole coupling. b From ref , 14 N quadrupole coupling constants. …”
Section: Rotational Spectra Of Piperidinementioning
confidence: 99%
See 1 more Smart Citation
“… a Transitions were deperturbed for 14 N and 2 H quadrupole coupling. b From ref , 14 N quadrupole coupling constants. …”
Section: Rotational Spectra Of Piperidinementioning
confidence: 99%
“…Another consideration is that isotopic substitution in oblate tops may cause significant rotation of the PAS and consequent problems with structure fitting . On the favorable side, a full set of ground state (GS) rotational constants is now available for all the heavy atom isotopologues of piperidine and the ND variant from microwave (MW) spectroscopy. New MW observations reported in this paper improve this set of GS rotational constants. The structure of piperidine has been investigated by gas-phase electron diffraction (GED) by Gundersen and Rankin …”
Section: Introductionmentioning
confidence: 99%
“…The low temperature dielectric relaxation study of Gilchrist et al (1988-837) also indicates an envelope structure for pyrrolidine. They reported the pseudo-rotational potential parameters, VI = 4.06 kJ'mol-1 and V2 = 4.69 kJ•mol-l • The microwave studies of Pf~fferott et al (1985Pf~fferott et al ( -1415 and Ehrlichmann et al (1989Ehrlichmann et al ( -1058 reported the existence of only one conformer, the envelope form with the imino H in the axial position. Pfafferott et al comment, that if the equatorial conformer exists, its rotational spectrum is very weak and the energy difference between the two isomers could nul be estimated.…”
Section: Pyrrolidinementioning
confidence: 99%
“…In this work we assume the existence of only axial conformer. The rotational constants reported by Ehrlichmann et al (1989Ehrlichmann et al ( -1058 were used to calculate the moments of inertia (Table 23). The symmetry number of external rotation is one.…”
Section: Pyrrolidinementioning
confidence: 99%
See 1 more Smart Citation